Efforts to Improve Early Childhood Language Skills through the Singing Method at RA Al-Hikmah - Jannah, Jumrotul (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the language skills of early childhood learners at RA Al-Hikmah through the implementation of singing-based instructional methods. Early language development is critical for cognitive, social, and academic growth, yet many young learners face challenges in vocabulary acquisition, pronunciation, and expressive communication. Singing has been recognized as an effective pedagogical strategy to stimulate linguistic and cognitive development by combining rhythm, melody, and repetitive phrasing, which support memory and oral expression. The research employed a Classroom Action Research (CAR) design, conducted in two cycles, each comprising planning, action, observation, and reflection stages. The participants were 25 children aged 4–6 years, and data collection involved observation sheets, language performance assessments, and audio-visual documentation. The findings revealed a significant improvement in children’s language abilities after the implementation of the singing method. In the initial observation, only 28% of students demonstrated age-appropriate expressive language skills. After the first cycle, this increased to 60%, and by the second cycle, 88% of children achieved marked improvement in vocabulary, sentence formation, pronunciation, and communicative confidence. Moreover, the observation indicated increased engagement, attention span, and social interaction among students during learning activities. These results suggest that singing methods are an effective, engaging, and developmentally appropriate strategy for enhancing early childhood language skills, supporting both cognitive and socio-emotional growth.